2022
DOI: 10.22323/2.21070206
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and societal goals in tension? A survey of communication practitioners at Swiss higher education institutions

Abstract: The public communication of higher education institutions (HEIs) has gained importance both in practice and research and can serve different goals. Many scholars argue that HEI communication departments mainly aim to promote their organization and are less concerned with broader societal goals and normative principles of communication. Since these assumptions have not yet been explored empirically, we surveyed 203 communication practitioners from all 42 Swiss HEIs on their role conceptions and the quality crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…To explain these differences, the affordances of the social media platforms and their user groups as well as the strategic aims of HEI communication may play a role. Nevertheless, recent research on the goals of HEI communication found only small differences between HEI types (Fürst et al, 2022b), insinuating that aims of communication are an implausible explanation. Further research into the influence of social media platforms on HEI communication is needed to confirm and better understand structural differences in communication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To explain these differences, the affordances of the social media platforms and their user groups as well as the strategic aims of HEI communication may play a role. Nevertheless, recent research on the goals of HEI communication found only small differences between HEI types (Fürst et al, 2022b), insinuating that aims of communication are an implausible explanation. Further research into the influence of social media platforms on HEI communication is needed to confirm and better understand structural differences in communication.…”
Section: Discussionmentioning
confidence: 99%
“…In line with Raupp (2017, p. 149), we understand the strategic communication of HEIs as their "intentional, internally and externally directed communication that serves to maintain and expand their organizational legitimacy." However, as mentioned previously, in the context of increasing expectations from society to fulfill the "third mission," HEIs not only pursue organizational goals but also societal goals, such as fostering dialogue and supporting open science initiatives (Fürst et al, 2022b). Social media platforms have become an integral part of the strategic communication of HEIs across the world.…”
Section: Strategic Communication Of Heis Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…Peters (2022), drawing on numerous similar diagnoses from the past few decades, emphasizes that the public communication efforts of many HEIs have moved toward a corporate model. Like other scholars before him, he argues that this trend can lead to clashes with the normative foundation of other models of science communication, for example, when HEIs uncritically promote organizational developments and achievements to boost public reputation, exaggerate the findings of studies conducted in-house, or do not disclose their limitations and scientific uncertainties (Fürst, Volk, Schäfer, Vogler, & Sörensen, 2022b;Sumner et al, 2014;Weingart, 2017). The study by Fürst and colleagues (2022a) in this Thematic Section illustrates this development: In Switzerland, most HEI leaders see the creation of a good image and a positive public reputation as one of the main goals of their organization.…”
Section: Dysfunctional Trends In Hei Communicationmentioning
confidence: 99%
“…Wie in vielen anderen OECD-Ländern haben die vor rund drei Jahrzehnten einsetzenden New Public Management-Reformen das Schweizer Hochschulsystem stark verändert. Diese gehen mit einem erhöhten Legitimationsdruck und einem wachsenden Wettbewerb um öffentliche Sichtbarkeit einher(Friedrichsmeier / Fürst 2012;Fürst et al 2022a).Nach Durchführung eines Pretests (siehe dazuFürst et al 2022b) und der Erstellung einer Kontaktliste von allen Kommunikator:innen in zentralen Kommunikationsabteilungen von Schweizer Hochschulen führten wir im Herbst 2020 eine Online-Befragung durch. Der Fragebogen war in Deutsch, Französisch und Italienisch verfügbar.…”
unclassified